Case Report on Full Term Normal Delivery - Pradnya Gavhale1 , Shalini Moon2 , Manoj Patil3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Labor has been defined as that of the initiation of periodic painful contractions of progressivedeletion as well as dilation of a cervix, followed by a decent part going to lead to the expulsion of its fetus& placenta from the uterus of mother. Post - natal treatment was its individualized treatment provided thatmeet the needs of the baby and mother after delivery/childbirth.Case Report: Mrs. Nikita Matram 25-year-old female was admitted in AVBR Hospital with the complaintof pain in abdomen and increased the fetal movement on date 4/01/2020 and she delivered female baby ondate 6/01/2020 and the baby weight was 2.8 kg at 1:40 am now her complaint was pain on suture side andweakness. but the patient has a previous history of abortion after marriage of four month two and half monthof baby was abort. That time dilatation and curettage was done.Patient delivered female baby throughout the vaginal delivery and baby and mother was normal afterdelivery baby was kept with mother on same bed and initiate breastfeeding within one hour after delivery.Conclusion: Case report conclude that after normal delivery and post-natal care mother and baby wasnormal.